НЕЙРОМОТОРНАЯ КОРРЕКЦИЯ В РАБОТЕ С ДЕТЬМИ С ОСОБЫМИ ОБРАЗОВАТЕЛЬНЫМИ ПОТРЕБНОСТЯМИ - Сапарбаева, М.А.; Бекманова, Ж.А. (SCIENCE and SOCIETY, 2025)
This article analyzes theoretical and practical aspects of the use of neurocorrective exercises in the context of neuropsychological correction. The essence of neurocorrection as an interdisciplinary approach aimed at restoration and development of higher mental functions through activation of brain neuroplasticity is revealed.